An information technology for the support for solving the analysis problem of the customers’ value within the enterprise CRM-strategy implementation - Orlovskyi, D. L.; Kopp, A. M.; Pyvovarova, A. A. (НТУ "ХПІ", 2019)
This study considers a CRM-approach and methods for analyzing customer base. Mathematical and algorithmic support was developed for the analysis of customer value in a trading enterprise. Algorithmic support is presented using the IDEF0 notation. A software solution was developed to assess customer value in a commercial enterprise. A fragment of the data model for the software solution was developed using the IDEF1x notation. The parameters for estimating the value of customers in a commercial enterprise were calculated using the processed data obtained by applying the developed software solution. The developed software solution allows to segment the customer base according to different criteria and provide marketing recommendations to each groups of customers. Therefore, customers were divided into groups according to the calculated parameters. As a result of the analysis, each group of clients receives a marketing recommendations. After the application of recommendations an increase in the purchasing power of clients, belonging to the group to which the marketing recommendation has been provided, is expected. Another used method for analyzing the customer base in the developed software solution is the sales funnel, which displays the effectiveness of the marketing unit at each of the sales stages, thereby allowing to identify weak points in the sales department. Thus, unlike existing software solutions, the developed software allows not only to segment customers by their costs, but also to provide marketing recommendations in order to increase the enterprise’s profit. The generation of recommendations is based on the developed mathematical support. By using this mathematical support, the calculations are carried out. Customers are allocated into certain groups, each of which is provided with the relevant marketing recommendations, by using the results of the performed calculations. In addition, the developed software solution allows not only to design sales funnels, but also to analyze sales funnels.

Розглянуто CRM-підхід і методи аналізу клієнтської бази. Було розроблено математичне та алгоритмічне забезпечення аналізу цінності клієнта в торговому підприємстві. Алгоритмічне забезпечення представлено в нотації IDEF0. Було розроблено програмне рішення для оцінки цінності клієнта в торговому підприємстві. На його основі розроблений фрагмент моделі даних в нотації IDEF1x. На основі опрацьованих даних за допомогою розробленого програмного рішення розраховуються параметри оцінки цінності клієнтів в торговому підприємстві. Розроблене програмне рішення дозволяє сегментувати клієнтську базу за різними критеріями та формувати маркетингові рекомендації для кожної групи клієнтів. Виходячи з розрахованих параметрів, клієнти діляться на групи. В результаті аналізу, кожна група клієнтів отримує маркетингову рекомендацію. Після застосування рекомендації очікується підвищення купівельної здатності клієнтів, що відносяться до групи, до якої була надана маркетингова рекомендація. Ще одним використовуваним методом аналізу клієнтської бази в розробленому програмному рішенні є воронка продажів, яка відображає ефективність роботи маркетингового підрозділу на кожному з етапів продажу, тим самим дозволяючи виявити слабкі місця в роботі відділу продажів. Таким чином, на відміну від існуючих рішень, розроблене програмне забезпечення дозволяє не тільки сегментувати клієнтів за їх вартістю, але й надавати маркетингові рекомендації для збільшення прибутку підприємства. Формування рекомендацій здійснюється на основі розробленого математичного забезпечення, на основі якого виконуються розрахунки, за результатами яких клієнти розподіляються на певні групи, кожній з яких надаються відповідні маркетингові рекомендації. Крім того, розроблене програмне рішення дозволяє виконувати не тільки побудову воронок продажів, а й їхній аналіз.
Інформаційна технологія підтримки процесу оцінки цінності клієнта в рамках реалізації CRM-стратегії підприємства
Keywords: client; customer classification; value analysis; sales funnel; класифікація клієнтів; аналіз цінності; воронка продажів